Diverse roles of the CIPK gene family in transcription regulation and various biotic and abiotic stresses: A literature review and bibliometric study - Yang, Chen; Yi-feng, Jin; Yushu, Wang; Yansong, Gao; Qi, Wang; Xue, You (Frontiers in Genetics, 2022)
A subclass of serine/threonine (Ser/Thr) protein kinases is termed as CIPKs. CBL are ubiquitous Ca2+ sensors that interact with CIPK with the aid of secondary messengers Ca2+ for regulation of growth, development, and responding to various stresses faced by plants. There are divergent roles of CIPK-CBL interaction in plants such as responding to environmental stress (salt stress, cold stress, drought stress, pH stress, ABA signaling, ion toxicity), ion homeostasis (K+ homeostasis, NH4+ homeostasis, NO3− homeostasis, Microelement homeostasis), biotic stress, and plant development. Each member of this gene family produces distinct proteins. They help plants adapt to diverse stresses or stimuli by interacting with calcium ion signals. CIPK consists of two structural domains an N-terminal domain and a C-terminal domain connected by a junction domain. The N-terminal domain is the site of phosphorylation also called the activation domain and kinase domain. The C-terminal also known as the regulatory domain of CIPK further comprises NAF/FISL and PPI. CBL comprises four EF domains and conserved PFPF motifs which is the site of binding with the NAF/FISL domain of CIPK making a complex of CBL-CIPK. Similarly, in this study, we have performed a bibliometric analysis of CIPK gene family. Data was extracted from the WOSCC. A total of 95 documents were retrieved; that been published by 47 sources. The production over time was zigzagged. Among the key terms, “gene”, “CIPK”, “abiotic stress”, “gene expression” etc were the leading terms. Beijing Forestry University stands on the top among the affiliations and “The Plant Cell” among the sources. This gene family has much more to be studied in terms of their genomics and metabolomics analysis.